Publications Rates for Podium and Poster Presentations From the American Orthopaedic Foot & Ankle Society: 2008-2012. (May 2017) - Williams, Benjamin R.; Kunas, Grace C.; Deland, Jonathan T.; Ellis, Scott J.
Background: National orthopaedic meetings are used to disseminate current research through podium and poster abstract presentations. Not all of these abstracts go on to full-text journal publication. The purpose of this study was to determine the publication rates of podium and poster presentations from the American Orthopaedic Foot & Ankle Society (AOFAS) annual meetings between 2008 and 2012. Methods: All accepted podium and poster abstracts from the 2008-2012 AOFAS annual meetings were compiled from the AOFAS office, Physician Resource Center website, and hardcopy meeting programs. PubMed and Google Scholar searches were performed for journal publications using key words in the presentation abstracts and authors' names. Full-text journal publication rates for the presentations were calculated per year, as were the most common journals of publication. Results: Overall full-text publication rate was 73.7% for podium presentations and 55.8% for posters. Podium presentations were published in a journal significantly more often than posters ( P < .0001; odds ratio 2.17 [95% confidence interval (CI), 1.64-2.86]). The mean time to publication was 1.5 and 1.4 years for podium and poster presentations, respectively ( P = .124). The most common journal for podium and poster publications was Foot & Ankle International . Conclusion: Podium abstracts were significantly more likely to be published compared to posters. The AOFAS overall full-text journal publication rate was one of the higher reported rates compared with other national orthopedic society meetings, which have ranged from 34% to 73%.